Payment System Revolution and Monetary Policy in the Face of Goods Price Transformation: The Effect of Non-Cash Transactions, Interest Rates, and Exchange Rates on Indonesian Inflation - Rahmansyah Harum; Indra Maipita; Fitrawaty Fitrawaty (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of non-cash transactions, interest rates, and exchange rates on inflation in Indonesia in the period from January 2021 to December 2023. Using the Error Correction Model (ECM) approach, this study examines the short-term and long-term relationships between these variables. The results of the study indicate that non-cash transactions have a negative and significant effect on inflation in both the short and long term, indicating that the development of digital payment systems can increase economic efficiency and suppress inflation. Meanwhile, interest rates do not have a significant effect on inflation in the short or long term, while exchange rates have a positive and significant effect on inflation in the long term. These findings provide important implications for monetary policymakers in an effort to maintain price stability amidst the transformation of the digital payment system.